People skills at work - Berman, Evan M. (CRC Press, 2012)
An exploration of the ways in which people skills can be acquired and developed, this book discusses new career development tools, the role of professional commitment statements, psychological contracts, and how to work with difficult people. Each chapter elucidates the development of a specific skill and includes examples, sets benchmarks, and examines how the particular skill's relationship to the other skills presented in the book. The author covers how to improve interpersonal relationships, communications, job performance, and dealing with people of different ages, gender, and backgrounds.